Female ESL teachers’ challenges at the tertiary level in India: An analysis during pre-pandemic, pandemic, and post-pandemic - Rani, Daisy; Venkatalakshmi, Shrimathy (Research Journal in Advanced Humanities, 2025)
This study explores the effectiveness of female English language teachers at the tertiary level in India in achieving optimal results with students from diverse socio-economic backgrounds during the pre-pandemic, pandemic, and post-pandemic periods. Women in the 21st century have made significant strides across professions, contributing notably to the socio-economic growth of the country. Teaching, considered a noble and suitable profession, remains a preferred career choice for women in India. At the tertiary level, particularly in teaching English as a second language, teachers face numerous challenges; however, female educators encounter unique obstacles. This study examines these challenges in the Indian context, noting disparities in the distribution of female teachers at various educational levels and the initial hurdles in entering higher education. Once in the profession, teaching diverse students requires additional skills and adaptability. The COVID-19 pandemic further introduced significant shifts in the teaching-learning process. Using a qualitative research design, this study includes classroom observations (offline and online), informal interviews, and teacher questionnaires. Findings reveal the impact of domestic, social, and environmental factors on teaching effectiveness and highlight how female educators overcome these barriers by adapting, innovating, and managing multiple responsibilities, demonstrating resilience in ever-changing scenarios.